How do cultural differences affect communication in emergency situations on ships? - A study of how language barriers and cultural differences affect the performance of the crew during emergency situations - Haglund, Hugo; Lindahl, Alex (My University, 2023)
Sailing with a multicultural crew is common among seafarers, and it can be challenging due to cultural barriers. Misunderstandings will occur when seamen with different proficiency interact, and it might make it more challenging in emergency situations. Studies show that communication is the biggest problem when working with a multicultural crew. The aim of the study is to gain a deeper understanding of how cultural differences affect emergency situations on board, while limiting the study to only internal ship situations and not ship-to-ship communication. Stress, sleep and other psychological limitations will not be studied. Semi-structured qualitative interviews with a strategic homogenous selection in person were used to gather information. The sailors interviewed were of Scandinavian descent, but all were of different ages, backgrounds, and experience. The questions asked consisted of five categories: Background and experience, Emergency situations, Communication challenges, Hypothetical challenges, and questions about the impact of language and culture in the shipping industry. The results were that communication is a big problem, but the biggest problem in emergency situations was that the crew did not train enough together. Practicing of different emergency scenarios and continuously speaking English on board seemed to help the interviewed officers most.
Keywords: Shipping; Multicultural Crew; Emergency situations; Communication